Clinical nurses’ work procrastination and smartphone addiction: a potential profile study - Xue, Huiyuan; Jing, Songbin; Song, Xiaoren; Zhang, Fen; Liu, Xiaoli; Si, Xiaona (Frontiers in Psychology, 2024)
Objective: This study aims to explore the current state of work procrastination among clinical nurses and identify potential profile categories. It further analyzes the impact of mobile phone addiction and demographic factors on work procrastination among clinical nurses. Methods: Convenience sampling was employed to recruit participants from three tertiary hospitals in central China from October to November 2023. Surveys measuring nurses' work procrastination and smartphone addiction were distributed and collected through online platforms. Mplus 8.3 statistical software was used for latent profile analysis of clinical nurses' work procrastination, and SPSS 26.0 software was utilized for chi-square tests, rank-sum tests, and multi-classification logistic regression analyses. Results：The median total score for clinical nurses' work procrastination was 21.00 (17.00, 28.00), and three subgroups were identified: low procrastination (66.93%), medium-low procrastination (20.66%), and medium-high procrastination (12.41%). Additionally, logistic regression analysis revealed that smartphone addiction and department atmosphere were common influencing factors for medium-low and medium-high work procrastination. Hospitals with stricter management and nurses holding the position of head nurse were more likely to belong to the low work procrastination group. Nurses with higher incomes or those holding intermediate titles were more prone to medium-low work procrastination, while those experiencing career advancement difficulties were more likely to exhibit medium-high work procrastination (P < 0.05). Conclusion：Clinical nurses' work procrastination is generally at a medium-to-low level. Additionally, clinical nurses in surgical departments or those with intermediate titles exhibit higher levels of procrastination. Factors such as smartphone addiction, higher monthly income, tense departmental atmosphere, and unsuccessful career advancement are more likely to lead to work procrastination. Conversely, nurses in hospitals with strict management or those holding the position of head nurse exhibit lower levels of work procrastination. Therefore, nursing managers should pay close attention to the work procrastination behaviors of clinical nurses, actively monitor predictive factors among different groups, and provide psychological counseling and relevant training based on individual nurse circumstances. Additionally, it is also essential to focus on and improve departmental atmosphere and nurse smartphone addiction to enhance clinical nurses' work efficiency and reduce work procrastination.